Real-World Effectiveness of Triple Extrafine Fixed-Dose Combination with Beclomethasone/Formoterol/Glycopyrronium on Symptoms and Lung Function in COPD: A Systematic Review and Meta-Analysis - Rogliani P; Manzetti GM; Cazzola M; Calzetta L (International Journal of COPD)
Paola Rogliani,1 Gian Marco Manzetti,1 Mario Cazzola,1 Luigino Calzetta2 1Unit of Respiratory Medicine, Department of Experimental Medicine, University of Rome “Tor Vergata”, Rome, Italy; 2Respiratory Disease and Lung Function Unit, Department of Medicine and Surgery, University of Parma, Parma, ItalyCorrespondence: Paola Rogliani, Unit of Respiratory Medicine, Department of Experimental Medicine, University of Rome “Tor Vergata”, Via Montpellier 1, Rome, 00133, Italy, Tel +39 06 2090 4656, Email paola.rogliani@uniroma2.itIntroduction: Chronic obstructive pulmonary disease (COPD) is a significant global health issue characterized by persistent airflow limitation and inflammation. Triple fixed-dose combinations (FDCs) of inhaled corticosteroids (ICS), long-acting β 2-agonists (LABA), and long-acting muscarinic antagonists (LAMA) show promise by potentially enhancing bronchodilation and anti-inflammatory effects. Although randomized controlled trials (RCTs) provide efficacy data, they may not fully represent real-world clinical practice, highlighting the value of real-world evidence (RWE).Methods: This study conducted a systematic review and meta-analysis of prospective observational multicenter studies to evaluate the real-world effectiveness of a triple extrafine FDC containing beclomethasone dipropionate (BDP), formoterol fumarate (FF), and glycopyrronium (G) in moderate-to-severe COPD patients. Databases MEDLINE and SCOPUS were searched for relevant studies reporting on the COPD Assessment Test (CAT) score and forced expiratory volume in one second (FEV1).Results: The meta-analysis included seven studies with 5952 patients, indicating high methodological quality with Newcastle–Ottawa Scale scores ≥ 7. Results showed significant improvement in CAT scores (− 5.82 95% CI − 7.61 - − 4.03; P < 0.001) and FEV1 (127 mL 95% CI 42– 212; P < 0.001) for extrafine BDP/FF/G FDC compared to any prior treatments (ICS/LABA, ICS+LABA, LABA/LAMA, LABA+LAMA, multiple-inhaler triple therapy, single-inhaler triple therapy), exceeding minimal clinically important differences. Heterogeneity was significant, but Egger’s test suggested no significant publication bias.Conclusion: The triple extrafine BDP/FF/G FDC effectively improves health status and lung function in real-world COPD patients, supporting its use as a viable therapeutic strategy. Further research should explore long-term outcomes and investigate specific patient subgroups to optimize individualized treatment approaches.Keywords: COPD, symptoms, lung function, real-world evidence, meta-analysis